Influence of manufacturing methods and use of CoCr-based abutments on vertical and horizontal marginal fit and torque loss in implant-supported prostheses - João Pedro Justino DE OLIVEIRA LIMIRIO; Jéssica Marcela de Luna GOMES; Joel Ferreira SANTIAGO-JUNIOR; Cleidiel Aparecido Araújo LEMOS; Maria Cristina Rosifini Alves REZENDE; Eduardo Piza PELLIZZER (Journal of Applied Oral Science)
Abstract Objectives This in vitro study evaluated implant-supported single crowns with external connections fabricated using different techniques (cast and CAD/CAM) and materials (metal-ceramic and translucent zirconia) regarding vertical and horizontal marginal fit and torque loss before and after mechanical cycling. Methodology A total of 50 specimens prepared using cast (lost wax) and CAD/CAM were divided into five groups—MC (metal–ceramic crowns), ZrB (Co-Cr base, coping milled in zirconia and feldspathic ceramic veneering), Zr (coping milled in zirconia and feldspathic ceramic veneering), MZrB (Co-Cr base and monolithic translucent zirconia crown), and MZr (monolithic translucent zirconia crown)—and subjected to 5×10⁶ mechanical cycles at a 30° angle at 37°C, and an applied load of 150N at 2Hz. All crowns were screwed with a 30Ncm torque. Vertical and horizontal marginal misfit (measured using a 3D optical microscope) and torque loss were assessed before and after mechanical cycling. Statistical analyses used a significance value of 0.05. Results Before cycling, MC (93.93±22.84µm) and MZrB (66.12±11.87µm) (p<0.05) crowns showed significantly higher vertical marginal misfit values than Zr (49.92±3µm) and MZr (49.76±3,9µm). ZrB (59.96±4.66µm) crowns exhibited no statistically significant difference when compared with the other groups. MC crowns presented the highest horizontal marginal misfit values before and after cycling in group comparisons (p<0.05). MZrB had the highest torque loss (10N), with a statically significant difference when compared with MZr and Zr (p<0.05). Comparison between all groups showed no significant difference regarding the effect of mechanical cycling (p>0.05). Conclusion CAD/CAM manufacturing resulted in lower vertical and horizontal marginal misfit values, especially for monolithic translucent zirconia crowns (MZr) before and after mechanical cycling. All groups presented torque loss before and after mechanical cycling.